Westonci.ca offers fast, accurate answers to your questions. Join our community and get the insights you need now. Our platform provides a seamless experience for finding precise answers from a network of experienced professionals. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.
Sagot :
To find out which of the given expressions equals [tex]\( 14 \)[/tex], we need to individually calculate each sum and verify the resultant values.
Let's analyze each sum step by step:
### Expression (A): [tex]\(\sum_{k=1}^3 k\)[/tex]
This sum means we need to add up the integers from [tex]\(1\)[/tex] to [tex]\(3\)[/tex].
[tex]\[ \sum_{k=1}^3 k = 1 + 2 + 3 = 6 \][/tex]
So, [tex]\(\sum_{k=1}^3 k = 6\)[/tex].
### Expression (B): [tex]\(\sum_{k=1}^3 k^2\)[/tex]
This sum means we need to add up the squares of the integers from [tex]\(1\)[/tex] to [tex]\(3\)[/tex].
[tex]\[ \sum_{k=1}^3 k^2 = 1^2 + 2^2 + 3^2 = 1 + 4 + 9 = 14 \][/tex]
So, [tex]\(\sum_{k=1}^3 k^2 = 14\)[/tex].
### Expression (C): [tex]\(\sum_{k=1}^3 7k\)[/tex]
This sum means we need to add up the values obtained by multiplying each integer from [tex]\(1\)[/tex] to [tex]\(3\)[/tex] by [tex]\(7\)[/tex].
[tex]\[ \sum_{k=1}^3 7k = 7 \times 1 + 7 \times 2 + 7 \times 3 = 7 + 14 + 21 = 42 \][/tex]
So, [tex]\(\sum_{k=1}^3 7k = 42\)[/tex].
### Expression (D): [tex]\(\sum_{k=1}^{14} k\)[/tex]
This sum means we need to add up the integers from [tex]\(1\)[/tex] to [tex]\(14\)[/tex].
We can use the formula for the sum of the first [tex]\(n\)[/tex] natural numbers, [tex]\(\frac{n(n+1)}{2}\)[/tex]:
[tex]\[ \sum_{k=1}^{14} k = \frac{14 \times (14 + 1)}{2} = \frac{14 \times 15}{2} = 105 \][/tex]
So, [tex]\(\sum_{k=1}^{14} k = 105\)[/tex].
After performing all the calculations, we find that the expression which sums to [tex]\( 14 \)[/tex] is (B):
[tex]\[ \boxed{\sum_{k=1}^3 k^2} \][/tex]
Let's analyze each sum step by step:
### Expression (A): [tex]\(\sum_{k=1}^3 k\)[/tex]
This sum means we need to add up the integers from [tex]\(1\)[/tex] to [tex]\(3\)[/tex].
[tex]\[ \sum_{k=1}^3 k = 1 + 2 + 3 = 6 \][/tex]
So, [tex]\(\sum_{k=1}^3 k = 6\)[/tex].
### Expression (B): [tex]\(\sum_{k=1}^3 k^2\)[/tex]
This sum means we need to add up the squares of the integers from [tex]\(1\)[/tex] to [tex]\(3\)[/tex].
[tex]\[ \sum_{k=1}^3 k^2 = 1^2 + 2^2 + 3^2 = 1 + 4 + 9 = 14 \][/tex]
So, [tex]\(\sum_{k=1}^3 k^2 = 14\)[/tex].
### Expression (C): [tex]\(\sum_{k=1}^3 7k\)[/tex]
This sum means we need to add up the values obtained by multiplying each integer from [tex]\(1\)[/tex] to [tex]\(3\)[/tex] by [tex]\(7\)[/tex].
[tex]\[ \sum_{k=1}^3 7k = 7 \times 1 + 7 \times 2 + 7 \times 3 = 7 + 14 + 21 = 42 \][/tex]
So, [tex]\(\sum_{k=1}^3 7k = 42\)[/tex].
### Expression (D): [tex]\(\sum_{k=1}^{14} k\)[/tex]
This sum means we need to add up the integers from [tex]\(1\)[/tex] to [tex]\(14\)[/tex].
We can use the formula for the sum of the first [tex]\(n\)[/tex] natural numbers, [tex]\(\frac{n(n+1)}{2}\)[/tex]:
[tex]\[ \sum_{k=1}^{14} k = \frac{14 \times (14 + 1)}{2} = \frac{14 \times 15}{2} = 105 \][/tex]
So, [tex]\(\sum_{k=1}^{14} k = 105\)[/tex].
After performing all the calculations, we find that the expression which sums to [tex]\( 14 \)[/tex] is (B):
[tex]\[ \boxed{\sum_{k=1}^3 k^2} \][/tex]
Thank you for choosing our service. We're dedicated to providing the best answers for all your questions. Visit us again. We appreciate your time. Please come back anytime for the latest information and answers to your questions. Stay curious and keep coming back to Westonci.ca for answers to all your burning questions.